2015
DOI: 10.1007/978-3-319-15075-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and Decidability Results for Hybrid(ised) Logics

Abstract: Abstract. Adding to the modal description of transition structures the ability to refer to specific states, hybrid(ised) logics provide an interesting framework for the specification of reconfigurable systems. The qualifier 'hybrid(ised)' refers to a generic method of developing, on top of whatever specification logic is used to model software configurations, the elements of an hybrid language, including nominals and modalities. In such a context, this paper shows how a calculus for a hybrid(ised) logic can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The work reported here, extending as discussed below previous results introduced in the original conference paper [9], paves the way to an alternative approach in which verification can be carried on at the level of the hybridised logic itself. Even if a number of further questions has to be addressed to make it a pragmatic alternative, namely in what concerns complexity and possible circumventing heuristics, the paper introduces a first contribution.…”
Section: Motivation and Contextsupporting
confidence: 57%
“…The work reported here, extending as discussed below previous results introduced in the original conference paper [9], paves the way to an alternative approach in which verification can be carried on at the level of the hybridised logic itself. Even if a number of further questions has to be addressed to make it a pragmatic alternative, namely in what concerns complexity and possible circumventing heuristics, the paper introduces a first contribution.…”
Section: Motivation and Contextsupporting
confidence: 57%
“…Recent work [45] reports preliminary general results in this direction. In particular, it is shown that, whenever the base logic has the usual Boolean connectives, hybridisation preserves decidability, and furthermore, the generated calculus is sound and complete whenever the one for the base logic is.…”
Section: Concludingmentioning
confidence: 98%
“…Often such a study has been made on a case-by-case basis e.g. [11,26,27]. This paper, on the other hand, surveys a more general, functorial perspective using three different asymmetric combinations of logics as case-studies.…”
Section: Natural Transformationsmentioning
confidence: 99%